2021
DOI: 10.1039/d1nr04062f
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled rhomboidal ammonia monolayer confined in two vertically stacked graphene oxide/graphene nanosheets

Abstract: Confined water molecules have attracted widespread research interest due to its versatile phase behaviors. Ammonia (NH3, isoelectronic with water) molecules are also expected to realize the delicate self-assembled hydrogen-bonded network...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…All the NH 3 molecules still adopt a Y-shaped configuration observed in our previous study. 19 Further considering from their top-view structures in Figure 3b′,c′, the rhomboidal pattern within NH 3 monolayers still remains unchanged, and their difference in N•••N distances of two corresponding short adjacent sides can be negligible and that of two corresponding long sides is smaller than 0.018 Å. Noticeably, some NH 3 molecules own more space, when the interlayer distance between two GO nanosheets becomes larger under the 6% tensile strain.…”
mentioning
confidence: 89%
See 3 more Smart Citations
“…All the NH 3 molecules still adopt a Y-shaped configuration observed in our previous study. 19 Further considering from their top-view structures in Figure 3b′,c′, the rhomboidal pattern within NH 3 monolayers still remains unchanged, and their difference in N•••N distances of two corresponding short adjacent sides can be negligible and that of two corresponding long sides is smaller than 0.018 Å. Noticeably, some NH 3 molecules own more space, when the interlayer distance between two GO nanosheets becomes larger under the 6% tensile strain.…”
mentioning
confidence: 89%
“…We know that the oxygen-containing functional groups in GO sheets are diverse, mainly involving hydroxyl, epoxy, ether, or carbonyl in the basal plane and hydroxyl or carboxyl at the edge. , However, the synthesis conditions can be controlled to realize GO sheets with desirable O-containing groups . Hence, it is acceptable to build more ideal GO models with relatively uniform O-containing groups in computational simulations. ,, Based on that, the computational models of NH 3 monolayer@GO systems were generated and confirmed in our previous study . In order to further explore their piezoelectricity, five various GO monolayers are first considered here involving different oxygen-containing functional groups, such as hydroxyl/carbonyl, hydroxyl, ether, and epoxy, the same as in previous treatments .…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…However, as the simulated graphene confined 2D ice crystals are slightly rhomboidal, it was suggested that these structures may be an artifact of the presence of sodium chloride contamination. Later, six stable mono-, bi-, and tri-layer ices or amorphous ices were revealed by classical molecular dynamics (MD) simulations of water confined by graphene sheets. Very recently, both ab initio and machine learning potential based MD simulations of water within graphene nanocapillaries shown that a flat zigzag monolayer ice (ZZMI) consisting of an array of zigzag water chains is stable at high pressures. , …”
mentioning
confidence: 99%